Bycatch data from ichthyoplankton surveys reveal long-term trends in gelatinous zooplankton in the Norwegian and Barents Seas. (12th November 2021) - Yaragina, Natalia A; Stige, Leif Chr; Langangen, Øystein
ABSTRACT: Gelatinous zooplankton play important roles as consumers in marine food webs, but the spatial and temporal dynamics of them are difficult to quantify because their fragility makes accurate sampling by traditional gears challenging. As a result, accurately quantified long-term data series targeting this group are scarce. To shed light on the dynamics of three groups of gelatinous zooplankton (medusae, ctenophores, and chaetognaths), we present and analyse time-series on frequency of occurrence and a relative index of abundance for each group recorded as bycatch in ichthyoplankton surveys. The time-series represent two areas (southwestern Barents Sea and northeastern Norwegian Sea), two seasons (spring and summer), and a 35-years period (1959–1993). Results suggest that occurrences of medusae and ctenophores increased from spring to summer in ocean shelf areas, whereas chaetognaths were ubiquitous in both seasons with highest abundance in oceanic areas. Spring occurrences correlated positively with summer occurrences for medusae and chaetognaths but not ctenophores, implying longest prediction horizon for the two first groups. The occurrence of medusae, but not ctenophores and chaetognaths, was consistently higher in warm than cold years. These results suggest that the occurrence and potentially the role of medusae in this arcto-boreal environment is most profound in warm periods.